Hydrocarbon Specialisation and De-industrialisation in the Rentier Economy of Algeria - CHETIBI, Amel (Journal of Human Sciences, 2016)
This paper aims to display the natural specialisation in hydrocarbons in Algeria. It explores the nature of Algeria’s resource-based industrialisation strategy and the underlying reasons for its shortcomings which has led to de-industrialisation with focus on roughly the first 30 years after the independence when the de-industrialisation has occurred. It also examines the link between the abundant hydrocarbons and the economic development and attempts to answer the question: why a resource rich economy like Algeria cannot benefit from its additional income for the promotion of industrial diversification? We finally argue that the analytical framework provided by theories considering the resource endowment as such as the root of the problem, like the Dutch disease theory, does not provide sufficient explanation for the Algerian case.